2016
DOI: 10.1590/1983-40632016v4640436
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of low-temperature stress in rice seedlings

Abstract: Rice is a cold-sensitive crop, and its exposure to low-temperature stress, during germination and early seedling growth, can negatively affect the initial stand establishment. Substances that act as growth regulators can be used to mitigate this initial stress. Thus, the influence of gibberellic acid, thiamethoxam and a phytohormone was investigated at the growth variables and antioxidant enzyme activity of the 'Irga 424' and 'Puita Inta CL' rice cultivars, at low-temperature (17 ºC). The products act on the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
10
0
1
Order By: Relevance
“…Several studies reported the improvement of total phenolic, anthocyanins, and flavonoids content in Thai rice varieties during germination under the salinity (60-200 mM NaCl) (Chutipaijit et al, 2009(Chutipaijit et al, , 2011Daiponmak et al, 2010;Ghosh et al, 2011). The germination of cold sensitive rice seeds at 17 °C improved the antioxidant property of rice seedlings, especially lipid peroxidation, and superoxide dismutase activity, and further facilitated the accumulation of plant hormone gibberellic acid, which diminished the impact of cold stress (Grohs et al, 2016). The brown rice (cultivar Khao Hom Dam Sukhothai 2) germinated at 35 ± 0.5 °C exhibited the superior antioxidant property than the rice germinated at 30 ± 0.5 °C (Pitiwiwattanakul et al, 2011).…”
Section: Changes In the Phytochemical Content Of Gbr During Stress Comentioning
confidence: 99%
“…Several studies reported the improvement of total phenolic, anthocyanins, and flavonoids content in Thai rice varieties during germination under the salinity (60-200 mM NaCl) (Chutipaijit et al, 2009(Chutipaijit et al, , 2011Daiponmak et al, 2010;Ghosh et al, 2011). The germination of cold sensitive rice seeds at 17 °C improved the antioxidant property of rice seedlings, especially lipid peroxidation, and superoxide dismutase activity, and further facilitated the accumulation of plant hormone gibberellic acid, which diminished the impact of cold stress (Grohs et al, 2016). The brown rice (cultivar Khao Hom Dam Sukhothai 2) germinated at 35 ± 0.5 °C exhibited the superior antioxidant property than the rice germinated at 30 ± 0.5 °C (Pitiwiwattanakul et al, 2011).…”
Section: Changes In the Phytochemical Content Of Gbr During Stress Comentioning
confidence: 99%
“…Other reports have shown that antioxidant metabolites and enzymes also contribute to cold tolerance (Kuk et al, 2003;Grohs et al, 2016) and correlate with growth performance (Chakraborty and Bhattacharjee, 2015). Cells are the building blocks of the plant body and the regulatory units that integrate locally perceived chemical and physiological signals by genetically encoded molecular regulatory networks that ultimately control the growth process (Gonzalez et al, 2012;Kalve et al, 2014;Czesnick and Lenhard, 2015).…”
mentioning
confidence: 99%
“…They are composed of gibberellin (which acts directly on the germination process and cell elongation), gibberellic acid (which increases the production of alpha-amylase at the level of gene transcription) and alpha-amylase and beta-amylase (which are enzymes responsible for the initial degradation of starch) (Taiz et al 2017). The use of biostimulants also boosted the germination of rice and maize seeds under heat stress (Grohs et al 2016, Carmo et al 2021.…”
Section: Resultsmentioning
confidence: 99%